A human NDP-kinase B specifically binds single-stranded poly-pyrimidine sequences. - Hildebrandt, M (1995)
Recently, a DNA binding protein 'PUF' was purified that binds to a poly-pyrimidine rich element in the human c-myc promoter. Cloning of the corresponding gene surprisingly identified this putative transcription factor as isoform B of the enzyme nucleoside diphosphate kinase (NDPK-B) [Postel et al. (1993) Science, 261, 478-480], the product of the potential metastasis suppressor gene nm23-H2. Using different recombinant NDP kinases, we demonstrate by electrophoretic mobility shift analysis (EMSA) that the NDP kinase DNA binding properties are predominantly observed with human isoform B. Unlike typical DNA binding proteins that are involved in transcriptional regulation, binding occurs to single-stranded DNA rather than to a double-stranded oligonucleotide. As a consequence, complexes of single-stranded DNA and NDPK-B are generated from double-stranded oligonucleotide hybrids in an ATP independent manner. In addition to the c-myc element, NDPK-B is binding in vitro to a variety of poly-pyrimidine rich sequences including dC or dT homo-oligomers, (CT)n dinucleotide repeats, the initiator region of the Adenovirus major late promoter and even poly-pyrimidine rich RNAs. The possible consequences of these findings in understanding the multiple roles of NDP kinase are discussed.